Socio-Economic and Environmental Impact of Community-Based Tourism Development in the Province of Biliran - Jane Marie G. Inocencio (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to assess community-based tourism development's socio-economic and environmental impact in the Province of Biliran, Philippines. The research employed quantitative and qualitative methods to gain insights into the province's socio-economic and environmental impacts of community-based tourism. Data were collected from key informants, stakeholders, and local tour guides, as well as from surveys and focus group discussions. The results indicate that community-based tourism development has generally benefited the local communities in terms of economic gains, employment opportunities, and improved infrastructure. However, the research also revealed that the development of tourism in the province had had some adverse environmental impacts, such as increased pollution and destruction of natural resources. The study also revealed that local communities had not been adequately involved in the planning and managing of tourism development in the province, which has led to a lack of ownership over the development process and a lack of accountability for the impacts. The study concludes that a more proactive approach to tourism planning and management is needed to ensure that tourism development's socio-economic and environmental impacts are adequately addressed.